O099 Position and number of anchors in hip arthroscopy labrum repair: a systematic review. (22nd July 2022) - Samoutis, A; Lee, MH; Patel, A; Jaiswal, P
Abstract: Introduction: Hip labral tears are reported in 22–55% of patients with hip or groin pain. Operative treatment is necessary for most cases, via hip arthroscopy with the use of suture anchors. This systematic review aims to determine the optimal number and position of anchors in hip labral repair. Methods: Pubmed, Ovid & Embase were searched, and 2 researchers independently screened the 1, 304 results. Outcome measures such as procedures performed, number & (clockface) position of anchors, failure & articular involvement of anchors were extracted. Results: 5 studies were included in the analysis: 1 Cross-Sectional Study (1645 Hips, mean age (MA):33.7 years), 3 Retrospective case studies (491 hips, MA:31.0) and 1 Controlled Cadaveric study (32 cadaveric hips, MA:62.7). Chi-squared statistical analysis of 323 hips found a significant difference (X 2 (2, N = 323) = 17.88, p < .001) in the risk of articular involvement with the position of anchors at 11°-12° o'clock, 1°-2° and 3°-4°. There is an absolute risk reduction (ARR) of 19% with anchors positioned at 11°-12° compared to anchors positioned at 3°-4° (X 2 (1, N=178) =15.79, p < .001) and an ARR of 12% with anchors at 1°-2° compared to anchors positioned at 3°-4° (X 2 (1, N = 237) = 15.79, p < .0109). Additionally, by assessing 1645 operations it was found that for tears spanning >2 hours, a minimum of 2 anchors was placed. Conclusion: Placement of anchors in the 3°-4° o'clock position carries the highest risk for articular involvement. Small diameter anchors and careful placement can be used to minimize articular injury. Preferable positions of anchors are 11°-12°, furthermore, for tears spanning over 2 hours, a minimum of 2 anchors was placed. Take-home message: In Hip Arthroscopy labral repair, placement of anchors in the 3°-4° o'clock position carries the highest risk for articular involvement. Small diameter anchors and 2 hours. flexible anchor instrumentation can be used to minimize articular injury, furthermore, for tears spanning over 2 hours, a minimum of 2 anchors was placed.